How Global Are Olfactory Bulb Oscillations? - Kay, Leslie M. (American Physiological Society, 2010)
Previous studies in waking animals have shown that the frequency structure of olfactory bulb (OB) local field potential oscillations is very similar across the OB, but large low-impedance surface electrodes may have favored highly coherent events, averaging out local inhomogeneities. We tested the hypothesis that OB oscillations represent spatially homogeneous phenomena at all scales. We used pairs of concentric electrodes (200 μm outer shaft surrounding an inner 2–3 μm recording site) beginning on the dorsal OB at anterior and medial locations in urethane-anesthetized rats and measured local field potential responses at successive 200 μm depths before and during odor stimulation. Within locations (outer vs. inner lead on a single probe), on the time scale of 0.5 s, coherence in all frequency bands was significant, but on larger time scales (10 s), only respiratory (1–4 Hz) and beta (15–30 Hz) oscillations showed prominent peaks. Across locations, coherence in all frequency bands was significantly lower for both sizes of electrodes at all depths but the most superficial 600 μm. Near the pial surface, coherence across outer (larger) electrodes at different sites was equal to coherence across outer and inner (small) electrodes within a single site and larger than coherence across inner electrodes at different sites. Overall, the beta band showed the largest coherence across bulbar sites and electrodes. Therefore larger electrodes at the surface of the OB favor globally coherent events, and at all depths, coherence depends on the type of oscillation (beta or gamma) and duration of the analysis window.